Dominican engagement with the world: an ongoing process of prophetic dynamism - Regan, Hilary D. (Interface theology, 2023)
"The essays in this volume examine various aspects of Dominican life. There are essays on prayer, spirituality, historical and biblical pieces as well as a piece on the work on the work of publishing by Dominicans. The contributors come from different parts of the world and reflect different vocations within the Order"--Back cover